Classifying Schizotypy Using an Audiovisual Emotion Perception Test and Scalp Electroencephalography - Jeong, Ji Woon; Wendimagegn, Tariku W.; Chang, Eunhee; Chun, Yeseul; Park, Joon Hyuk; Kim, Hyoung Joong; Kim, Hyun Taek (Frontiers in Human Neuroscience, 2017)
Schizotypy refers to the personality trait of experiencing “psychotic” symptoms and can be regarded as a predisposition of schizophrenia-spectrum psychopathology (Raine, 1991). Cumulative evidence has revealed that individuals with schizotypy, as well as schizophrenia patients, have emotional processing deficits. In the present study, we investigated multimodal emotion perception in schizotypy and implemented the machine learning technique to find out whether a schizotypy group (ST) is distinguishable from a control group (NC), using electroencephalogram (EEG) signals. Forty-five subjects (30 ST and 15 NC) were divided into two groups based on their scores on a Schizotypal Personality Questionnaire. All participants performed an audiovisual emotion perception test while EEG was recorded. After the preprocessing stage, the discriminatory features were extracted using a mean subsampling technique. For an accurate estimation of covariance matrices, the shrinkage linear discriminant algorithm was used. The classification attained over 98% accuracy and zero rate of false-positive results. This method may have important clinical implications in discriminating those among the general population who have a subtle risk for schizotypy, requiring intervention in advance.